2021
DOI: 10.1016/j.clnesp.2021.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to COVID-19 nutritional guidelines and their impact on the clinical outcomes of hospitalized COVID-19 patients

Abstract: Background & Aims Coronavirus disease 2019 (COVID-19) patients are at high risk of malnutrition, and their doctors are part of a multidisciplinary team, including nutritionists. However, adherence to nutritional guidelines may be difficult in the context of capacity constraints during the COVID-19 pandemic. The aim of this study was to investigate barriers to doctors’ adherence to nutritional guidelines and the impacts of guideline adherence on the outcomes of hospitalized COVID-19 patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Even in tertiary care centers, inadequate implementation of nutritional care in patients with COVID-19 has been documented when compared to malnutrition prevalence [28,67]. In surveys from South-East Asia, limitations were confirmed in implementation of nutrition guidelines in COVID-19 patients, with reasons including lack of confidence as well as budget limitations [121]. Similarly, insufficient knowledge of nutrition management was self-reported by ICU personnel in a Swiss survey [122].…”
Section: Hurdles: Awarenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Even in tertiary care centers, inadequate implementation of nutritional care in patients with COVID-19 has been documented when compared to malnutrition prevalence [28,67]. In surveys from South-East Asia, limitations were confirmed in implementation of nutrition guidelines in COVID-19 patients, with reasons including lack of confidence as well as budget limitations [121]. Similarly, insufficient knowledge of nutrition management was self-reported by ICU personnel in a Swiss survey [122].…”
Section: Hurdles: Awarenessmentioning
confidence: 99%
“…Similarly, insufficient knowledge of nutrition management was self-reported by ICU personnel in a Swiss survey [122]. Importantly, low adherence to nutritional guidelines was associated with negative clinical outcomes including higher length of stay in ICU and mortality [121]. On the other hand, studies reporting adequate implementation of nutritional care in ICU to reach nutritional targets also reported good access to healthcare professionals such as nutritionists and dietitians [123e126].…”
Section: Hurdles: Awarenessmentioning
confidence: 99%
“…Other immunonutrients, including the amino acids glycine, arginine, and glutamine, may mitigate inflammation, protect lung and intestinal integrity during acute illness, and support muscle renewal during recovery (156). Unfortunately, the volatile status of the pandemic continues to limit clinical trials on COVID-19-specific nutrition recommendations, and some reports indicate suboptimal institutional adherence to existing guidelines (157)(158)(159). The completion of well-designed clinical trials and then creation and adoption of subsequent evidence-based guidelines is critically important for lowering mortality and shortening hospital stays (158).…”
Section: Chronic/post-covid-19mentioning
confidence: 99%
“…Unfortunately, the volatile status of the pandemic continues to limit clinical trials on COVID-19-specific nutrition recommendations, and some reports indicate suboptimal institutional adherence to existing guidelines (157)(158)(159). The completion of well-designed clinical trials and then creation and adoption of subsequent evidence-based guidelines is critically important for lowering mortality and shortening hospital stays (158).…”
Section: Chronic/post-covid-19mentioning
confidence: 99%
“…A study based on hospitalized patients indicated that the reason, behind not following doctors' guideline lack of nutritional knowledge, not attitudes or financial factors. 7 Making individuals understand the importance of nutritional practice is vital to make post-COVID situation better in case of regaining immunity. According to a survey done in China, inhabitants had a high awareness rate of most nutrition knowledge during the epidemic time, and a significant number of them adjusted their food safety and nutrition-related practices.…”
mentioning
confidence: 99%